Sie sind auf Seite 1von 3

Math F412: Homework 1 Solutions

January 28, 2005

1. Section 1-2
2.

The distance between and the origin at time t given by


|(t| =

1 (t)2 + 2 (t)2 + 3 (t)2 .

1
d
|(t| = (t
(t) 0 (t). At the closest point to 0, the derivative must vanish.
Hence dt
Hence (t) 0 (t) = 0. Since (t) 6= 0 and 0 (t) 6= 0, this implies the position vector (t)
is orthogonal to the tangent vector 0 (t).

4.

Notice that

d
d
(t) v = ( (t)) v + (t) v = 0 (t) v.
dt
dt
Since 0 (t) is orthogonal to v for all t, we conclude
d
(t) v = 0
dt
for every time t. So (t) v must be constant. Since (0) v = 0 we conclude that
(t) v = 0 for all t.
Note: do Carmo is defining vectors v and w to be orthogonal if v w = 0 and both v
and w are non-zero.

5.

Suppose |(t)| is a non-zero constant. Recall that


d
1
|(t)| =
(t) 0 (t)
dt
(t)
d
(This makes since because (t) 6= 0). Since dt
|(t)| = 0 we conclude that (t) 0 (t) = 0
for every time t. Since (t) 6= 0 and since 0 (t) 6= 0 we conclude (t) is orthogonal to
0 (t) for every time t.

Conversely, suppose (t) is orthogonal to 0 (t) for every time t. So (t) 6= 0, 0 (t) 6= 0,
and (t) 0 (t) = 0. Hence |(t)| =
6 0 and
d
1
|(t)| =
(t) 0 (t) = 0.
dt
(t)
So |(t)| is constant. Since (t) is non-zero, we conclude that |(t)| is a non-zero constant.

2. Section 1-3
2a.
We can break up the problem of describing the curve into a couple of pieces. First,
consider the curve (t) = ( sin(t), cos(t)). The trace of this curve is the unit circle, and
the curve traverses the circle clockwise with (t) = (0, 1). Now make the circle move to
the right so that when the curve has traversed the circle once, the circle has moved to the

Math F412: Homework 1 Solutions

January 28, 2005

right by one circumference. This is done by letting (t) = ( sin(t) + t, cos(t)). Finally,
scoot the curve up by one unit so that the circle rolls along the x-axis. This obtains the
parameterization (t) = ( sin(t) + t, 1 cos(t)). Since 0 (t) = 0 when both compoents
vanish, we see that the critical points must happen for those values of t where 1 cos(t) = 0
and sin(t) = 0. So t = 2k where k Z.
2b.

First, 0 (t) = (1 cos(t), sin(t)), so

0
(t)

(1

cos(t))2

+ sin (t) =

1 2 cos(t)

+ cos2 (t) + sin2 (t)

2 2 cos(t).

Then the length of the curve is


Z
2 2 cos(t) dt = 2

Z 2 q
0

2 q

1 cos(t) dt.

Next we make the substitution u = 1 cos(t), so du = sin(t) dt. We want to write the
sin(t) in terms of u. To do this it will be handy to write
Z 2 q
0

1 cos(t) dt = 2

On [0, ], sin(t) is positive and hence sin(t) =


have 1 cos2 (t) = 2u u2 . So
dt =

Z q

1 cos(t) dt.

1 cos2 (t). Since cos(t) = 1 u, we

1
1
du =
du.
sin(t)
2u u2

Using this substitution we obtain


2

Z q
0

1 cos(t) dt = 2

Z 2
0

1
du = 8.
2u

First, we note that on the domain (0, ), the function log(tan(t/2)) has no singularites.
So is smooth. Moreover,
4a.

sec2 (t/2)
(t) = cos(t), sin(t) +
2 tan(t/2)

!
1
= cos(t), sin(t) +
2 sin(t/2) cos(t/2)

!
1
= cos(t), sin(t) +
.
sin(t)
0

Now 0 (t) is zero if and only if its components both vanish. Notice that on the interval
1
= 1 + 1 = 0. So t = /2
(0, ), cos(t) = 0 only at t = /2. But sin(/2) + sin(/2)
is a critical point and is the only critical point.

Math F412: Homework 1 Solutions

4b.

January 28, 2005

The tangent vector is given by 0 (t)

= cos(t),

(t) is given by {(t) + s0 (t)

cos2 (t)
sin(t)

. For fixed t, the tangent space

at
: s R}. The point on the tangent line that intersects the
y-axis occurs when sin(t) + s cos(t) = 0, so s = tan(t). Finally, the distance between
(t) and (t) + s0 (t) is just |s0 (t)|. With s = tan(t),
s0 (t) = ( sin(t), cos(t))
Hence |s0 (t)| = 1 as required.
6a.

The curve can be written as (t) = aebt (cos(t), sin(t)). Now the curve
(t)
= (cos(t), sin(t))
|(t)|

just circles around the origin. Moreover, |(t)| = aebt , so radius goes to 0 as t tends to
infinity.
6b.

First,
0 (t) = a(bebt cos(t) ebt sin(t), bebt sin(t) + ebt cos(t))
= aebt (b cos(t) sin(t), b sin(t) + cos(t)).

Since ebt goes to 0 as t gets large, and since the other terms in 0 (t) are bounded, we
conclude 0 (t) 0 as t tends to infinity. Now

0
(t)

= aebt (b cos(t) sin(t))2 + (b sin(t) cos(t))2 .

A computation shows that


q

(b cos(t)

sin(t))2

+ (b sin(t) cos(t))2

So
Hence,

0
(t)
t0

0
(t)

1 + b2 .

= a 1 + b2 ebt .

Z q
t0

a 1 + b2 ebt =

a q
1 + b2 ebt0 .
b

Notice that b < 0 so 1/b > 0. Hence the length is positive and finite.